Arctic geology : proceedings of the Second International Symposium an Arctic Geology held February 1-4, 1971 at San Francisco, California - International Symposium on Artic Geology (2nd : 1971 : San Francisco, California) (Tulsa : American Association of Petroleum Geologists, 1973)
08